DEVELOP A COMMUNICATION PLAN TO HELP PREVENT TEENAGE PREGNANCY AND ENCOURAGING SEXUAL RESPONSIBILITY IN THE CITY GUAYAQUIL - Graf Barriga, María Patricia (2012)
The lack of communication and knowledge in adolescents is directly affecting the increase of teenage pregnancy in the city of Guayaquil. This research aims to find and understand the causes and emotional effects of teenage pregnancy and attitudes towards contraceptive methods. The research also aims at finding communication solutions. The investigation variables that were measured in this research are sexual education and teenage pregnancy. For the development of this research, primary data was gathered from interviews, surveys, case study and observations; and secondary data was gathered from literature and related articles. The following results had the most significant matter: 79% of the surveyed girls have not received any sex education from their parents, but 75% would like to able to talk about sex with them. It was also discovered that girls have misconceptions about certain contraceptive methods and negative connotations toward others; they associate condoms with promiscuity and sexual disease. A majority of girls (65%) consider the withdrawal method (coitus interruptus) to be effective, despite compelling evidence to the contrary. The misconceptions can be eliminated with effective communication between parents and daughters, as well as improved sex education.